Curitiba-Viewport: contribuição ao desenvolvimento de uma plataforma computacional para cidades virtuais - Miranda, Frederico Severo (2017)
Information and communication technologies (ICT’s) are present daily in the life of society and cause changes in the way they live. ICT’s enable the creation of new products and services to improve people’s lives. It has been used in work, relationships, public services, entertainment and leisure with the aim of mitigate social exclusion, improving economic performance, creating employment opportunities, improving quality of life and promoting social participation. In this context of technological developments and hyperconnectivity combined with concerns about sustainable urban growth, effective governance and better ways of analyzing and exploring data, a variety of research emerges taking into account the concepts of smart cities, digital cities and virtual cities. Noting the beneﬁts provided by smart, digital and virtual cities (from the perspective of a digital game) and the fact that there is currently no consolidated knowledge, nor a computational platform with the necessary resources to integrate applications associated with the physical environment of citizens that involve social, governmental, commercial, educational, scientiﬁc and entertainment aspects, this work seeks to answer the following question: is it possible to develop a virtual city in the perspective of a digital game with the purpose of being a platform for execution of applications that bring beneﬁts to the lives of citizens of a region? From this question, the present dissertation was organized in four layers of interests: technological, ethical, sociocultural and public actions. In relation to the development of the technological layer (focus of this dissertation), the project was divided into four main activities: graphic modeling, database creation, web server development and ﬁnally the development of the game itself . Taking into account the developed prototype and the results obtained, the C-VP proved to be a virtual city in the perspective of a digital game with the purpose of being a platform for application execution, thus answering the question that originated this dissertation.